Fungsi Humas Pemerintah Terkait Isu Kerentanan Vaksin Covid 19 pada Lansia di Indonesia - Pamungkas, David; Zebua, Winda Dwi Astuti (Educationist: Journal of Educational and Cultural Studies, 2024)
The issue of the vulnerability of the Covid-19 vaccine in the elderly is ultimately what causes many people to be reluctant to get the Covid-19 vaccine. This condition is one of the factors that can hinder the preventive efforts made by the Indonesian government to prevent transmission of the Covid-19 virus. This article aims to describe how the government public relations function of the Ministry of Health of the Republic of Indonesia in overcoming public concerns about the side effects of vaccines on the elderly. This article uses a qualitative method with a literature study approach, which is a study used to collect data and information needed with the help of various kinds of reading materials, both online journals, books, and documentation of communication efforts carried out by the public relations of the Ministry of Health of the Republic of Indonesia (Ministry of Health). RI). Furthermore, the data will be analyzed by making summaries and data reduction, then categorizing, and making conclusions. The findings from this article are that there are two functions of the Ministry of Health's public relations in handling the issue of the Covid 19 vaccine insecurity for the elderly, namely a constructive function and a corrective function. From these two functions, public relations for the Ministry of Health of the Republic of Indonesia needs to carry out persuasive and appropriate communication for the effectiveness of the corrective function, because in this case the issues that cause people's concern are widespread.